2021
DOI: 10.1007/s10666-021-09764-8
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure in Egypt: Empirical Evidence Based on a Quantile Regression Approach

Abstract: This paper investigates the key factors affecting household energy expenditure in Egypt. Based upon the latest 2015 Egyptian HIECS Survey, we develop a quantile regression model with an innovative variable selection approach via Adaptive Lasso Regularization technique to untangle the spectrum of household energy expenditure. Unsurprisingly, income, age, household size, housing size, and employment status are salient predictors for energy expenditure. Housing characteristics have a moderate impact, while socioe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The mean students' CF score increases with higher household income, confirming that higher consumption is correlated with a higher economic level. This finding was reinforced by Belaid and Rault, (2021) (49), who found that EGYPT energy expenditure positively correlates with household-income. Additionally, Lévay et al, (2021) (50), found income and household CF are strongly correlated.…”
Section: Discussionmentioning
confidence: 76%
“…The mean students' CF score increases with higher household income, confirming that higher consumption is correlated with a higher economic level. This finding was reinforced by Belaid and Rault, (2021) (49), who found that EGYPT energy expenditure positively correlates with household-income. Additionally, Lévay et al, (2021) (50), found income and household CF are strongly correlated.…”
Section: Discussionmentioning
confidence: 76%
“…on REC The role of urban form publications It affects the amount of REC [8,9,11,[14][15][16][17]19,[81][82][83][84][85][86] It does not affect the amount of REC [10,23,[71][72][73][74] The role of density on REC The role of density publications Positive correlation [34,35,40,54,67,75] Negative correlation [8,9,28,[30][31][32][33][36][37][38][39][41][42][43]46,47,[49][50][51][52]56,57,60,64,…”
Section: The Role Of Urban Formmentioning
confidence: 99%
“…Positive correlation [34,35,40,54,67,75] Negative correlation [8,9,28,[30][31][32][33][36][37][38][39][41][42][43]46,47,[49][50][51][52]56,57,60,64,66,68,[76][77][78] Not disclosed (Not. Sig) [29,45,48,53,55,59,61,62,65,[69][70][71][72][73][74]82] Note.…”
Section: The Role Of Density Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantile regression on the microeconomic level has already been used in income analysis (Demir et al, 2020) as well as household expenses (Belaid & Rault, 2021) and savings (Hua & Erreygers, 2019). Examples of applied quantile regression can also be found in studies on indebtedness focused on analysis of the amount of loan (Pastrapa & Apostolopoulos, 2015), debt repayments (Han & Shi, 2009), and debt-to-income ratio (Tseng & Hsiao, 2022).…”
Section: Analytical Strategymentioning
confidence: 99%